2021
DOI: 10.1002/smll.202100066
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Mechanically Enhanced Carbon Nanotube Fibers by Silk Fibroin Infiltration

Abstract: Natural materials, such as silk, nacre, and bone, possess superior mechanical properties which are derived from their unique hierarchical structures. Individual carbon nanotubes (CNTs) are considered as one of the strongest materials. However, macroscopic CNT fibers usually have breaking strength far below that of individual CNTs. In this work, by mimicking the structure of natural silk fibers, strong and stiff CNT fibers are prepared by infiltrating silk fibroin (SF) into CNT fibers. There are abundant hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…[17][18][19][20][21] CNT yarns are especially promising candidates due to their high strokes, electrical conductivity, thermal conductivity, and mechanical strength. [22,23] When This angle decreases to zero in going from yarn surface to yarn center, which means that the material near yarn center consumes energy without making much contribution to muscle stroke. [24,26] The weight of needed CNTs can be reduced by fabricating sheath-run muscles (SRAMs), [30] which deploy a twisted CNT yarn as the core and a polymer guest as the sheath.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] CNT yarns are especially promising candidates due to their high strokes, electrical conductivity, thermal conductivity, and mechanical strength. [22,23] When This angle decreases to zero in going from yarn surface to yarn center, which means that the material near yarn center consumes energy without making much contribution to muscle stroke. [24,26] The weight of needed CNTs can be reduced by fabricating sheath-run muscles (SRAMs), [30] which deploy a twisted CNT yarn as the core and a polymer guest as the sheath.…”
Section: Introductionmentioning
confidence: 99%
“…4b), showing increased breaking strength up to 1023 MPa (+ 250%), improved toughness from 7.8 to 10.3 MJ m -3 (+ 132%), and Young's modulus of 81.3 GPa (+ 442%). 94 MD simulation indicated that the glycerol-accessional -sheet of SF along with abundant hydrogen bonds between SF and CNTs contributed to enhancing the mechanical property of the CNTs fibers. To construct the assembled CNTs yarns with higher mechanical property, inspired by the mechanical exercising-induced hierarchical structure of human muscle, through cyclic stretching training (cyclic stretching or cyclic loading), Xu et al firstly created a novel microstructure-reorganized strategy to fabricate a hierarchical CNTs bundle and CNTs thread mechanical organizing structure (Fig.…”
Section: The Cnts-assembled Structuresmentioning
confidence: 98%
“…Reproduced with permission. 94 Copyright 2021, Wiley-VCH. (c) Bioinspired microstructurereorganized behavior of CNT yarn.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…[16,42] The structure of the protein determines its physical and biological properties, in that the 𝛽-sheet crystalline regions of SF give it good mechanical properties (Figure 1) while the hydrophilic regions makes it elastic. [9,12,39,43] The biopolymer SS, acting as a glue-like protein in the cocoon, is composed of 18 amino acids [20] and has a molecular weight that can vary between 10 and 350 kDa. [28] Serine, a hydrophilic amino acid, represents one third of the total composition of SS.…”
Section: Structure and Physicochemical Propertiesmentioning
confidence: 99%